Utilization of Used Frying Oil in the Making of Soap: Effect of Saponification Time and a Dextrin Concentration - Wijana, Susinggih; Mustaniroh, Siti Asmaul; Wahyuningrum, Indha (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
The research was aimed to find out the best treatment in the making of soap from used frying oil and to analyze its financial feasibility. A randomized factorial block design was used in the experiment. The soap was made by saponifying at various length of time (30; 45, and 60 minutes) and dextrin concentrations of 1 %; 2.5 %; 4 % respectively. The yields as well as some characteristics of the soap, namely moisture content, the level of free alkali, pH, texture, and middle length of the foam were determined. A sensory evaluation was also performed on the colour and texture of the soap. A financial analysis was carried out to determine the values of Break Even Point (BEP), Payback Period, and Return of Investment (ROI) on the manufacturing of the selected method of soap production. It was found that the best soap was obtained by applying a 30 minutes saponification process combined with the use of 1% dextrin with the soap yield of 87.51% and having the following characteristics: moisture content 7.31 %, free alkali content 0.1279 %, pH 10.4, the texture 0.0007 mm/g.sec., and the foamâ€™s middle length of 2.15 cm. However, the panelists tends to be like nor dislike to the colour and texture of the product. The value of BEP is 50,387 units at a value of Rp.13,574,333.00, which was equivalent with a production capacity of 45 kg/day. The respective values of Payback Period and ROI were 50 months (4 years and 2 months) and 18.49 %. Â Key words: used frying oil, soap, saponification, dextrin